Properties of hydrogenated amorphous carbon films deposited by PECVD and modified by SF6 plasma - Marins, N. M. S. [UNESP]; Mota, Rogério Pinto [UNESP]; Honda, Roberto Yzumi [UNESP]; Nascente, P. A. P.; Kayama, M. E. [UNESP]; Kostov, K. G. [UNESP]; Algatti, M. A. [UNESP]; Cruz, N. C. [UNESP]; Rangel, E. C. [UNESP] (Elsevier B.V. Sa, 2011)
Hydrogenated amorphous carbon (a-C:H) films were grown at room temperature on glass and polished silicon substrates using RF-PECVD (Radio-Frequency Plasma Enhanced Chemical Vapor Deposition). Plasmas composed by 30% of acetylene and 70% of argon were excited by the application of RF signal to the sample holder with power ranging from 5 to 125W. After deposition, the films were submitted to SF6-plasma treatment for 5 minutes. SF6 plasmas were generated at a pressure of 13.3 Pa by a RF power supply operating at 13.56 MHz with the output fixed at 70 W. The resulting films were characterized in terms of their molecular structure, chemical composition, surface morphology, thickness, contact angle, and surface free energy. During the SF6 plasma treatment, fluorine species were incorporated in the film structure causing chemical alterations. The interaction of chemical species generated in the SF6 plasmas with surface species was responsible for the decrease of the film thickness and surface energy, and for the increase of the film roughness and hydrophobicity. Published by Elsevier B.V.
Keywords: Sulfur hexafluoride plasma treatment; RF-PECVD; a-C:H films; Wettability; Roughness; Chemical composition